(untitled) (INTERNATIONAL JOURNAL OF APPLIED SCIENCE & TECHNOLOGY, 2021)
Outsourcing is a well-defined phrase based on comparative advantage and labour division notions. However, outsourcing has a wide range of consequences, both domestically and internationally, including considerable political ramifications related with job migrations. The interface of multiple national business environments in such transnational cooperation is a multilayered process including divergent legal, economic, and social concerns. This essay will focus on the importance of understanding sharing in offshore outsourcing contacts, as well as the vital role of intellectual property (IP) in enabling and assisting it.